An inconvenient truth a global warning - Guggenheim, Davis; David, Laurie; Bender, Lawrence; Burns, scott Z.; Paramount Classics; Participant Productions (Hollywood, CA : Paramount Pictures, 2006)
Al Gore explains the contributing factors to the growing climate crisis, describes changes to the environment caused by global warming, and discusses the shift in environmental policy that is needed to avert disaster
Title from container
Indonesian subtitles
Executive producer, Jeff Skoll...[et al.] ; music by Michael Brook ; edited by Jay Cassidy, Dan Swietlik
Keywords: Global warming; Climatic changes; Human ecology; Greenhouse effect, Atmospheric